Allometric relationships for estimating vegetative and reproductive biomass in grapevine (Vitis vinifera L.). (25th April 2017) - Miranda, C.; Santesteban, L.G.; Escalona, J.M.; De Herralde, F.; Aranda, X.; Nadal, M.; Intrigliolo, D.S.; Castel, J.R.; Royo, J.B.; Medrano, H.
Abstract: Background and Aims: Vineyards, one of the most widespread agricultural systems, have significant but scarcely evaluated carbon sequestration potential. Allometry is a cost‐effective approach to estimate plant biomass, but few studies – focused mainly on permanent structure carbon fixation – have dealt with it in grapevine. This study develops allometric models that accurately estimate grapevine standing biomass (total vine biomass at harvest), using extensive field‐collected data sets. Methods and Results: Data were obtained in vineyards located in Spanish regions representative of the variability found in warm semi‐arid Mediterranean regions. We developed and validated functions to estimate vine biomass for all vine organs. The models obtained estimated accurately the biomass fixed by each organ separately and even more accurately at the whole plant scale. To illustrate the potential of the models, they satisfactorily assessed the influence of seasonal vine water status on vine biomass production and partitioning using an independent data set. Conclusions and Significance of the Study: The models constitute a powerful tool to determine in a non‐destructive and cost‐effective manner standing biomass from simple vine measurements, which makes them suitable for quantifying carbon stocks and allocation patterns, and for evaluating the influence of climate or cultural practices at large scale to estimate better – at a regional or international level – the contribution of grapevine culture to CO2 balances.